Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1152/ajpendo.1979.236.6.e769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on intestinal calcium absorption and adaptation to dietary calcium.

Abstract: To study the reported decline in intestinal calcium absorption with age, calcium active transport, immunoreactive calcium protein (CaBP) content, and alkaline phosphatase activity were measured in the intestine of two strains of rats aged 3-wk--20 mo. Calcium active transport, as measured by everted gut sacs from Sprague-Dawley rats, was greatest at 3 wk, but it declined rapidly with no active transport demonstrable at 3 mo or thereafter. CaBP content closely paralleled the decline in active transport, but alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 17 publications
3
39
0
1
Order By: Relevance
“…absorption expressed as percent of intake), whereas high intake is associated with low fractional absorption. This adaptive response has been demonstrated in various animal species (4,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) as well as in adult man (24, 35, 361, but not in infants. It involves the active, saturable component of calcium absorption (27,32) and is vitamin D dependent (25,37).…”
mentioning
confidence: 90%
“…absorption expressed as percent of intake), whereas high intake is associated with low fractional absorption. This adaptive response has been demonstrated in various animal species (4,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) as well as in adult man (24, 35, 361, but not in infants. It involves the active, saturable component of calcium absorption (27,32) and is vitamin D dependent (25,37).…”
mentioning
confidence: 90%
“…The second purpose of the study was to compare the conver- sion of 25-OH-D3 to 1,25-(OH)2-D3 in the mammalian kidney of young and adult rats. The rat was used because the intestinal absorption of calcium (8), the plasma levels of 1,25-(OH)2-D3 (9), and the intestinal levels of the vitamin D-stimulated calcium-binding protein (CaBP) (8,10) all decrease with age in the rat. The results of these experiments indicated that there was a marked decrease in the intestinal response of the vitamin D-deficient adult rat to 25-OH-D3.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease may correspond to a decrease in the organism's requirement with age. Armbrecht et al (27) indicated that the active transport component of the absorption mechanism declined with age. The saturable process developed rapidly beginning at 18d of age and peaked at 20 to 40d (28).…”
Section: Discussionmentioning
confidence: 99%